Preparation and characterization of microcapsules containing industrially important reactive water-soluble polyamine - Shukla, Parshuram G.; Jagtap, Siddheshwar B.; Biradar, Satish C.; Charpe, Vaibhav P.; Jadhav, Arun S. (Colloid and Polymer Science, 2016)
Polyurea microcapsules containing water-soluble reactive polyamine, namely, polyaziridine (A33), were prepared by interfacial polymerization technique in non-aqueous medium, wherein (i) A33 was encapsulated for the first time as a neat amine without forming its salt or adduct and (ii) microcapsules formed were without any deleterious effect on A33. A systematic study was conducted by preparing microcapsules with different polyurea wall architectures. Fourier transform infrared (FTIR) and proton nuclear magnetic resonance (H-1 NMR) spectroscopic analysis of extracted A33 from microcapsules do not show any structural changes during microencapsulation. A titration method was developed to analyze the amount of encapsulated A33 quantitatively. Polyurea microcapsules obtained from reaction of ethylene diamine (E) and isophorone diisocyanate (I) monomers have shown better properties such as encapsulation efficiency and extent of agglomeration. Significant reduction in the size was observed when microcapsules of EI wall material were prepared by homogenizing the initial emulsion of A33 in paraffin oil. The process described in this paper for the preparation of microcapsules is cost-effective and industrially viable, which can find applications in agrochemicals, coatings, self-healing composites, etc.